ONLAYN OAV VA IJTIMOIY TARMOQLAR O‘RTASIDAGI AXBOROT OQIMLARI: O‘ZARO INTEGRATSIYA VA NAZORAT (Neo Scientific Peer Reviewed Journal, 2025)
This article analyzes the integration and control mechanisms of information flows between online mass media (OMM) and social networks. As mass media expand their traditional news delivery functions in the digital environment, the speed of content distribution and the impact on audiences through social platforms are increasing. The article explores the mutual influence of these two information spaces, their interaction in information exchange, algorithmic filtering based on artificial intelligence, and the processes of content monitoring. In addition, the article highlights urgent issues related to ensuring reliable information, combating fake news, and maintaining information security.